Peripherally inserted central catheter-related thrombosis rate in modern vascular access era-when insertion technique matters: A systematic review and meta-analysis - Balsorano, Paolo; Virgili, Gianni; Villa, Gianluca; Pittiruti, Mauro; Romagnoli, Stefano; De Gaudio, Angelo Raffaele; Pinelli, Fulvio (The journal of vascular access, 2020)
Technical factors at the moment of catheter insertion might have a role in peripherally inserted central catheter-related thrombotic risk. We performed a systematic review and meta-analysis to define the actual rate of peripherally inserted central catheter-related symptomatic deep vein thrombosis in patients in whom catheter insertion was performed according to ultrasound guidance, appropriate catheter size choice, and proper verification of tip location. We searched Medline, Embase, and Cochrane Library. Only prospective observational studies published in peer-reviewed journals after 2010 up to November 2018 reporting peripherally inserted central catheter-related deep vein thrombosis rate were included. All studies were of adult patients who underwent peripherally inserted central catheter insertion. Results were restricted to those studies which included in their methods ultrasound guidance for venipuncture, catheter tip location, and a catheter size selection strategy. Random-effect meta-analyses and transformation for binomial data were performed to pool deep vein thrombosis weighted frequencies. Of the 1441 studies identified, 15 studies involving 5420 patients and 5914 peripherally inserted central catheters fulfilled our inclusion criteria. The weighted frequency of peripherally inserted central catheter-related deep vein thrombosis was 2.4% (95% confidence interval = 1.5-3.3) and remained low in oncologic patients (2.2%, 95% confidence interval = 0.6-3.9). Thrombotic rate was higher in onco-hematologic patients (5.9%, 95% confidence interval = 1.2-10). Considerable heterogeneity (I = 74.9) was observed and all studies were considered at high risk of attrition bias. A proper technique is crucial at the moment of peripherally inserted central catheter insertion. Peripherally inserted central catheter-related deep vein thrombosis rate appears to be low when evidence-based technical factors are taken into consideration during the insertion procedure.